Peran Profitabilitas, Leverage, dan Kebijakan Deviden `Terhadap Kinerja Keuangan Perusahaan - Ida Ayu Kade Yamunawati; I Nyoman Putra Yasa (Vokasi : Jurnal Riset Akuntansi, 2024)
The purpose of this research is to determine the influence of the cost of good sold, financial ratios, and dividend policy on the financial performance of technology companies listed on the BEI for the 2020-2022 period. The data in this research was obtained through the official website of the Indonesian stock exchange, namely www.idx.co.id. The sampling technique uses a purposive sampling technique with 26 technology sector companies listed on the IDX. The data collection method in this research is through financial report data from technology companies listed on the IDX.. The hypothesis test includes multiple linear regression analysis, t test, F test and coefficient of determination with the help of the IBM SPSS 26 for Windows application. The results of this research show that the variables cost of good sold, financial ratios, and dividend policy have a positive and significant effect on financial performance.